Exploring the Complexities of Urbanization and Socio-Ecological Challenges in the High Mountainous Region of Chitral, Khyber Pakhtunkhwa (KPK), Pakistan - Shahab Uddin; Anila Kausar; Sheeba Afsar; Ambreen Afzal; Altaf Hussain Lahori; Olena Stepova; Muhammad Mushahid Anwar; Viktor Bredun (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2023)
Rapid urbanization is not only an issue in plain areas but also in mountainous regions. However, urbanization affects the socio-ecological pattern of mountainous regions especially depleting natural resources, e.g., traditional agricultural practices. Although urban sprawl impinges on such fertile productive lands, it also positively affects trade activities, and high-income opportunities, and the region will have high spatial interaction. This paper presents the results of an attempt to gain insight into the mechanisms for the urban growth of district Chitral (Chitral Town) located in the Hindu Kush range north of KPK Pakistan. Over the last few decades, the urban agglomeration has become attractive among migrants from within and beyond the district, further accelerating urban growth in the surrounding area. The landscape transformation phenomenon in Chitral town was investigated with the following objectives: (i) Detection of spatiotemporal change in the study area over the last two decades, (ii) Identification of existing landscape patterns i.e. land-use assessment by analysing the acquired high-resolution remote satellite imageries for the years 2003 and 2020, (iii) Empirical analysis of data within the framework of an object-based approach. Land-use transformations like spatiotemporal change, loss of agriculture, and infrastructure patterns of urban growth were estimated for the past 17 years. This study reveals that the agricultural Land-use has declined by 348 m2 while the Built-up area has increased by 318 m2. The research offers practical recommendations for sustainable town planning and management. As such, this study has the potential to propose future strategies and it may be helpful to the policy/decision-makers in the development of future town planning in the similar mountainous regions of Pakistan or elsewhere.